The Art of Making Everybody Happy : How to Prevent a Secession - Le Breton, Michel (IMF Working Papers; Working Paper ;, 2001)
In this paper we consider a model of the country with heterogeneous population and examine compensation schemes that may prevent a threat of secession by dissatisfied regions. We show that horizontal imbalances are combatable with secession-proof compensation schemes that entail a degree of partial equalization: the disadvantageous regions should be subsidized but the burden on advantageous regions should not be too excessive. In the case of uniform distribution, we establish the 50-percent compensation rule for disadvantageous regions. Thus, we argue for a limited gap reduction between advantageous and disadvantageous regions and show that neither laissez faire nor Rawlsian allocation is secession-proof.